No changes in soil organic carbon and nitrogen following long-term prescribed burning and livestock exclusion in the Sudan-savanna woodlands of Burkina Faso - Aynekulu, Ermias; Sileshi, Gudeta W.; Rosenstock, Todd S.; Noordwijk, Meinevan; Tsegaye, Diress; Koala, Jonas; Sawadogo, Louis; Milne, Eleanor; Leeuw, Jan de; Shepherd, Keith D. (Elsevier, 2021)
Fire and overgrazing reduce aboveground biomass, leading to land degradation and potential impacts on soil organic carbon (SOC) and total nitrogen (TN) dynamics. However, empirical data are lacking on how prescribed burning and livestock exclusion impact SOC in the long-term. Here we analyse the effects of 19 years of prescribed annual burning and livestock exclusion on tree density, SOC and TN concentrations in the Sudanian savanna ecoregion at two sites (Tiogo and Laba) in Burkina Faso. Results revealed that neither livestock exclusion nor prescribed burning had significant impact on SOC and TN concentrations. The results at both sites indicate that 19 years of livestock and fire exclusion did not result in a significant increase in tree density compared to grazing and annual prescribed burning. The overall mean (± SEM) of SOC stocks in the 0–50 cm depth increment in the unburnt (53.5 ± 4.7 Mg C ha−1) and annually burnt (56.4 ± 4.3 Mg C ha−1) plots at Tiogo were not statistically different. Similarly, at Laba there was no significant difference between the corresponding figures in the unburnt (37.9 ± 2.6 Mg ha−1) and in the annually burnt plots (38.6 ± 1.9 Mg ha−1). Increases in belowground inputs from root turnover may have countered changes in aboveground biomass, resulting in no net change in SOC and TN. We conclude that, contrary to our expectation and current policy recommendations, restricting burning or grazing did not result in increase in SOC stocks in this dry savanna ecosystem.